Matrix Metalloproteinases: Inflammatory Regulators of Cell Behaviors in Vascular Formation and Remodeling - Qishan Chen; Min Jin; Feng Yang; Jianhua Zhu; Qingzhong Xiao; Li Zhang (Mediators of Inflammation)
Abnormal angiogenesis and vascular remodeling contribute to pathogenesis of a number of disorders such as tumor, arthritis, atherosclerosis, restenosis, hypertension, and neurodegeneration. During angiogenesis and vascular remodeling, behaviors of stem/progenitor cells, endothelial cells (ECs), and vascular smooth muscle cells (VSMCs) and its interaction with extracellular matrix (ECM) play a critical role in the processes. Matrix metalloproteinases (MMPs), well-known inflammatory mediators are a family of zinc-dependent proteolytic enzymes that degrade various components of ECM and non-ECM molecules mediating tissue remodeling in both physiological and pathological processes. MMPs including MMP-1, MMP-2, MMP-3, MMP-7, MMP-8, MMP-9, MMP-12, and MT1-MMP, are stimulated and activated by various stimuli in vascular tissues. Once activated, MMPs degrade ECM proteins or other related signal molecules to promote recruitment of stem/progenitor cells and facilitate migration and invasion of ECs and VSMCs. Moreover, vascular cell proliferation and apoptosis can also be regulated by MMPs via proteolytically cleaving and modulating bioactive molecules and relevant signaling pathways. Regarding the importance of vascular cells in abnormal angiogenesis and vascular remodeling, regulation of vascular cell behaviors through modulating expression and activation of MMPs shows therapeutic potential.